A 2'-alkynylnucleotide strategy for site-directed spin labelling of DNA - Haugland, M (2016)
This thesis describes the synthesis of derivatives of 2'-ethynyl-2'-deoxynucleosides, and their conversion into phosphoramidite building blocks for DNA synthesis. Herein is also outlined the preparation of azide-bearing nitroxyl radicals. After site-selective incorporation of 2'-alkynylnucleosides into DNA using a standard solid-supported phosphoramidite protocol, the modified oligonucleotides were spin labelled with the azide-bearing nitroxyl spin labels via the Cu(I)-catalysed azide-alkyne [3+2] Huisgen cycloaddition (CuAAC or 'click' reaction). The destabilising effect of the spin labelling was determined by UV denaturation studies and circular dichroism, and the spin labelled DNA was investigated by EPR spectroscopy. It was found that this novel site-directed spin labelling strategy afforded conformationally restricted systems, and that the structure of the spin label exerts a significant influence on the results.